Suberin composition of reproduction cork from Quercus suber - García Vallejo, M C; Conde, E; Cadahía, E; DeSimon, B F (HOLZFORSCHUNG, 1997)
The monomeric composition of suberins from Spanish Quercus suber was determined by gas chromatography/mass spectrometry in the product of depolymerization of free extractives cork with sodium methoxide-methanol. 1-Alkanols (C-20-C-26)(1.8-6.4%), alkanoic acids (C-20-C-24)(2.2-8.1%), alpha,omega-alkanedioic acids (C-16-C-24)(6.1-10.2%) and omega-hydroxy-alkanoic acids (C-20-C-26, being C-22 and C-24 the most abundant)(28.7-37.3%) are identified. The erythro- and threo-9,10-dihydroxyoctadecanedioic (5.4-7.5%), erythro- and threo-9,10,18-trihydroxyoctadecanoic (7.6-11.8%), 9,10-epoxy-18-hydroxyoctadecanoic (1.2-3.1%) and 9,10-epoxy-octadecanodioic acids (1.0-4.4%) and the unsaturated 18-hydroxy-9-octadecenoic (8.1-11.5%) and 9-octadecenedioic (1.5-2.4%) acids are also important components. Ferulic acid (5.3-9.1%) is the main phenolic component of suberin. The studied samples differ in the relative proportion of the different monomers.
Keywords: Cork; epoxy acids; fatty alcohols; fatty and hydrixy-fatty acids; gas chromatography; gas chromatography/mass spectrometry; phenolics; Quercus suber; suberin